Lateral‐compartment Osteophytes are not Associated With Lateral‐compartment Cartilage Degeneration in Arthritic Varus Knees. Issue 5 (May 2017) - Waldstein, Wenzel; Kasparek, Maximilian F.; Faschingbauer, Martin; Windhager, Reinhard; Boettner, Friedrich
Abstract: Background: Progression of arthritis in the lateral compartment is one of the main failure modes of unicompartmental knee arthroplasty (UKA). The decision regarding whether to perform a medial UKA sometimes is made based on whether lateral‐compartment osteophytes are visible on plain radiographs obtained before surgery, but it is not clear whether the presence of lateral‐compartment osteophytes signifies that the cartilage in the lateral compartment is arthritic. Questions/purposes: (1) Is the presence of lateral compartment osteophytes associated with biomechanical properties of lateral‐compartment cartilage, and (2) are osteophytes in the lateral compartment associated with particular histologic features of cartilage in the lateral compartment? Methods: Between May 2010 and January 2012, we performed 201 TKAs for varus osteoarthritis confirmed on standardized AP hip‐to‐ankle standing radiographs . All patients with a varus deformity were considered for this prospective study. During the enrollment period, 100 patients (101 knees) were not enrolled for this study because of declined consent or because they were unable to perform all required preoperative radiographic examinations. That left 84 patients (100 knees), of whom an additional 23 patients (27%) were excluded because either radiographic or biomechanical data were missing. For final analysis, 61 patients (71 knees) were available. There were 29 males (48%) and 32 females (52%) with a mean age of 65 years (range, 49‐89 years). Their mean BMI was 26 kg/m 2 (range, 17‐47 kg/m 2 ). Lateral‐compartment osteophytes were graded by two observers on AP standing knee radiographs based on a template of the Osteoarthritis Research Society International (OARSI) radiographic atlas. During surgery, osteochondral plugs were harvested from the lateral tibial plateau and the distal lateral femur for biomechanical and histologic assessments. The intrinsic material coefficients aggregate modulus (Ha) and dynamic modulus (DM) were determined by applying a compressive load of 20 g for 1 hour. The histologic analysis was performed according to the qualitative osteoarthritis cartilage histopathology assessment system. The Mann‐Whitney U test was performed to compare the distribution of variables. Power analysis was performed for the Mann‐Whitney U test using an alpha of 0.05, a power of 80%, and a sample size of 71 resulting in a detectable effect size of 0.6. Owing to the limited sample size, only medium or large effects in changes of biomechanical properties can be excluded with adequate power. Results: Ha and DM were not different with the numbers available when comparing knees with osteophyte Grades 0, 1, and 2 on the lateral tibia. For Grade 3 tibial osteophytes (n = 3), the lateral tibia cartilage showed low Ha (0.39 MPa; SD, 0.17 MPa) and low DM (2.85 MPa; SD, 2.12 MPa). On the lateral femur, no differences of Ha and DM were observed with the numbers available between Grades 0 to 3 osteophytes. No differences with the numbers available in the OARSI histologic grades on the lateral tibia plateau and the distal lateral femur were observed between the different osteophyte grades. Conclusions: Lateral‐compartment osteophytes are not associated with biomechanically weaker cartilage or with more‐advanced histologic signs of degeneration of lateral‐compartment cartilage in knees with varus arthritis. Given the small sample size of 71, the study was underpowered to detect small‐to‐modest decreases in biomechanical properties. Future studies with larger sample sizes are needed to confirm the current findings. Clinical Relevance: Factors other than the presence or absence of lateral‐compartment osteophytes should be considered when evaluating patients with medial‐compartment arthritis for medial UKA. Future studies are required to define the limitations of plain radiographs to rule out cartilage degeneration in the lateral compartment of varus knees.